Definition Ethics Of Early Childhood Teachers - Sari, Zona Junita; Despi, Despi; Rahmadani, Jesi Pitriya; Fadilla, Rohayu (Jurnal Pendidikan Rafflesia, 2025)
The ethics of Early Childhood Education (ECE) teachers represent a set of moral principles, social norms, and professional responsibilities that guide teachers’ behavior in carrying out their educational duties (Fitriani, 2019). ECE teachers play a strategic role in instilling moral values, character, and positive habits from an early age (Yuliani, 2019). This article aims to describe the definition of teacher ethics in ECE, its fundamental principles, and its role in supporting professionalism and children’s character development (Sari & Wibowo, 2023).The study employs a literature review approach, analyzing scholarly sources such as journals, books, and professional ethics guidelines (Damayanti & Nugraha, 2020). The findings indicate that teacher ethics play a crucial role in creating a positive learning environment, strengthening emotional–social relationships between teachers and children, and enhancing the moral image of the teaching profession (Marlina & Setiawan, 2021; Handayani & Rahmawati, 2022).